Modulation of the complex regulatory network for methionine biosynthesis in fungi. Issue 2 (11th January 2021) - Shrivastava, Manjari; Feng, Jinrong; Coles, Mark; Clark, Benjamin; Islam, Amjad; Dumeaux, Vanessa; Whiteway, Malcolm
Abstract: The assimilation of inorganic sulfate and the synthesis of the sulfur-containing amino acids methionine and cysteine is mediated by a multibranched biosynthetic pathway. We have investigated this circuitry in the fungal pathogen Candida albicans, which is phylogenetically intermediate between the filamentous fungi and Saccharomyces cerevisiae . In S. cerevisiae, this pathway is regulated by a collection of five transcription factors (Met4, Cbf1, Met28, and Met31/Met32), while in the filamentous fungi the pathway is controlled by a single Met4-like factor. We found that in C. albicans, the Met4 ortholog is also a core regulator of methionine biosynthesis, where it functions together with Cbf1. While C. albicans encodes this Met4 protein, a Met4 paralog designated Met28 (Orf19.7046), and a Met31 protein, deletion, and activation constructs suggest that of these proteins only Met4 is actually involved in the regulation of methionine biosynthesis. Both Met28 and Met31 are linked to other functions; Met28 appears essential, and Met32 appears implicated in the regulation of genes of central metabolism. Therefore, while S. cerevisiae and C. albicans share Cbf1 and Met4 as central elements of the methionine biosynthesis control, the other proteins that make up the circuit in S. cerevisiae are not members of the C. albicans control network, and so the S. cerevisiae circuit likely represents a recently evolved arrangement.